The Influence of Green Accounting Implementation and Environmental Performance on Firm Value - Sri Daryanti Zen; Amirah Zahra Ariri (Return : Study of Management, Economic and Bussines, 2025)
This research aims to test, analyze and empirically prove the influence of green accounting and environmental performance on company value in basic materials sector companies listed on the Indonesia Stock Exchange in 2021-2023 with a population of 107 companies. The research sample was selected using a purposive sampling technique according to the criteria so that a sample of 20 companies was obtained. This research uses the SPSS version 29 application to test sample data for each variable. This research is causality research with a quantitative approach that uses secondary data collected from annual financial reports and company continuity reports obtained from the official website of the Indonesia Stock Exchange www.idx.co.id and which can be obtained from the respective company websites. The results of the green accounting study measured by the environmental cost ratio have a significant effect on company value. While the environmental performance variable measured by the PROPER rating does not have a significant effect on company value. The novelty in this study is that the green accounting variable is seen from the environmental costs measured using the formula environmental costs / net profit after tax. While previous studies, environmental costs were measured using dummy variables. Then the company value variable was measured using Tobin's Q. However, in this study the company value variable was measured using Price to Book Value (PBV).